2017
DOI: 10.3389/fcimb.2017.00314
|View full text |Cite
|
Sign up to set email alerts
|

Unique Chemokine Profiles of Lung Tissues Distinguish Post-chemotherapeutic Persistent and Chronic Tuberculosis in a Mouse Model

Abstract: There is a substantial need for biomarkers to distinguish latent stage from active Mycobacterium tuberculosis infections, for predicting disease progression. To induce the reactivation of tuberculosis, we present a new experimental animal model modified based on the previous model established by our group. In the new model, the reactivation of tuberculosis is induced without administration of immunosuppressive agents, which might disturb immune responses. To identify the immunological status of the persistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…S11), essential coreceptors for the TDM-induced immune response which have been associated with impaired innate recognition of Mtb in T2D mice (47). Furthermore, CCL12, intracellular NOD2, and lysosomal cathepcin C, all of which have been implicated in immunity to Mtb (22,48,49), were also found to be significantly down-regulated in T2D mice. Major transcriptomic changes were observed following Mtb infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…S11), essential coreceptors for the TDM-induced immune response which have been associated with impaired innate recognition of Mtb in T2D mice (47). Furthermore, CCL12, intracellular NOD2, and lysosomal cathepcin C, all of which have been implicated in immunity to Mtb (22,48,49), were also found to be significantly down-regulated in T2D mice. Major transcriptomic changes were observed following Mtb infection.…”
Section: Discussionmentioning
confidence: 98%
“…Among those, 312 genes were mutually differentially regulated in TB/T2D and TB mice. These include genes previously found in blood and lung transcriptome profiles from TB patients and Mtbinfected mice, respectively (21,22). In addition, 124 DEGs were differentially expressed between T2D and naïve control mice.…”
Section: Differential Immune Gene Expression Patterns Following Mtb Imentioning
confidence: 98%
“…27 Previous studies have suggested that CCL7 was up-regulated in active tuberculosis patients and was down-regulated in post-chemotherapeutic treated mouse tuberculosis model. 28,29 Moreover, in Leishmania major infection, CCL7 was found to be an inflammatory regulator in different organs. 30 Therefore, CCL7 may be a potential target for the host-directed treatment of infectious granulomatous disease.…”
Section: Discussionmentioning
confidence: 99%